2020
DOI: 10.37939/jrmc.v24i3.1482
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Hepatic Vein Resistive Index in Detection of Hepatic Fibrosis in Patients of Chronic Liver Disease

Abstract: Introduction: If we could prove the diagnostic accuracy of hepatic vein resistive index in detecting liver fibrosis in chronic liver disease patients, this would be beneficial for the patients as it is a non-invasive, readily available, and cost-effective technique for the diagnosis of liver fibrosis. This will help the physicians in the early initiation of definitive management. Materials and Methods: Seventy-five (n=75) patients with hepatitis B aged between 18-50 years were enrolled. Hepatic vein resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In our study, the majority of the population were males which is in line with the previous studies done by Selvamuthukumaran and Kanitkar et al [ 9 , 17 ]. The mean age of the study participants in our study was consistent with the findings of Nadeem et al and Kanitkar et al [ 17 , 18 ]. The bleeding, shock, organ dysfunction, and respiratory distress in severe dengue subjects were in line with the observations of a study by Diwakar and Madhu [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the majority of the population were males which is in line with the previous studies done by Selvamuthukumaran and Kanitkar et al [ 9 , 17 ]. The mean age of the study participants in our study was consistent with the findings of Nadeem et al and Kanitkar et al [ 17 , 18 ]. The bleeding, shock, organ dysfunction, and respiratory distress in severe dengue subjects were in line with the observations of a study by Diwakar and Madhu [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…In corroboration to our result, Petchiappan et al [ 21 ] reported a direct association between hyperferritinemia and severe dengue, with a rise in serum ferritin levels starting on day four of illness. In a study conducted by Nadeem et al, patients with severe dengue fever exhibited significantly higher mean serum ferritin levels of 317.54±109.52 ng/mL, than patients with uncomplicated dengue fever (168.69±130.7 ng/mL) [ 18 ]. Similar observations were also made by Kanitkar et al [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar result was also seen in the paper on dengue infection in the Aruba Islands by Brazilian and the Dutch medical researcher for rise in SGOT and SGPT [9] . Nadeem et al 2016 [8] , showed hyper ferritinaemia in dengue fever indicates highly active disease resulting in immune activation. There occur reactive hepatitis and ischemic insult to hepatic cell in dengue shock syndrome, which causes rise in liver enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…However, estimation of such prognostic markers should require less technical expertise, be cost‐effective, and be able to provide an accurate prediction at an early time point of infection so that appropriate measures can be taken to prevent disease progression. Multiple studies have reported the association of serum ferritin levels with the severity of dengue disease 11,19–42 . Assays for the estimation of serum ferritin are easy to perform and comparatively less expensive, and serum ferritin levels may be considered as a prognostic marker to predict severe dengue.…”
Section: Introductionmentioning
confidence: 99%